Parallel Session 3: Acute/Vascular/Trauma| Wed 18 May, 1445 – 1600|4 Circulating Interleukin-6 predicts carotid study. Issue 9 (12th August 2022) - Kamtchum-Tatuene, Joseph; Saba, Luca; Heldner, Mirjam; Poorthuis, Michiel HF; Borst, Gert de; Rundek, Tatjana; Kakkos, Stavros; Chaturvedi, Seemant; Topakian, Raffi; ,
Abstract : Background and Aims: Interleukin-6 (IL-6) has important roles in atherosclerosis pathophysiology. To determine if anti-IL-6 therapy could be an adjuvant stroke prevention strategy in patients with carotid atherosclerosis, we tested whether circulating IL-6 levels predict carotid plaque severity, vulnerability, and progression in the Cardiovascular Health Study. Methods: Carotid ultrasound was performed at baseline and 5 years. Plaque severity was scored 0 to 5 based on NASCET grade of stenosis. Plaque vulnerability at baseline was the presence of irregular, ulcerated or echolucent plaques. Plaque progression at 5 years was a ≥1 point increase in stenosis severity. Relationship of plasma IL-6 levels with plaque characteristics was modeled using multivariable linear (severity) or logistic (vulnerability and progression) regression. Risk factors of atherosclerosis were included as independent variables. Results: In 4334 participants with complete data (58.9% women, 72.7 ± 5.1 years). There were 1267 (29.2%) participants with vulnerable plaque and 1474 (34.0%) with plaque progression. Log IL-6 predicted plaque severity (β = 0.09, p=0.04), vulnerability (OR = 1.22, 95% CI: 1.06-1.40, p=0.006) and progression (OR = 1.44, 95% CI: 1.23-1.69, p<0.001). In participants with >50% probability of progression, mean log IL-6 was 0.54 corresponding to 2.0 pg/mL. Dichotomizing IL-6 levels did not affect performance of regression models. Conclusions: Plasma IL-6 predicts carotid plaque severity, vulnerability, and progression. The 2.0 pg/mL cut-off could help select individuals that would benefit from anti-IL-6 drugs for stroke prevention.